2020
DOI: 10.1073/pnas.1912367117
|View full text |Cite
|
Sign up to set email alerts
|

Nitrifier adaptation to low energy flux controls inventory of reduced nitrogen in the dark ocean

Abstract: Ammonia oxidation to nitrite and its subsequent oxidation to nitrate provides energy to the two populations of nitrifying chemoautotrophs in the energy-starved dark ocean, driving a coupling between reduced inorganic nitrogen (N) pools and production of new organic carbon (C) in the dark ocean. However, the relationship between the flux of new C production and the fluxes of N of the two steps of oxidation remains unclear. Here, we show that, despite orders-of-magnitude difference in cell abundances between amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
102
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 58 publications
19
102
1
Order By: Relevance
“…The radiocarbon signatures of thaumarchaeal DNA demonstrated that MGI members derive the majority of their carbon from inorganic carbon fixation from the same site (Hansman et al, 2009). A recent quantitative study of the amoA and accA genes in the western Pacific revealed similar distributional trends at depths greater than or equal to 100 m as those documented in our study (Zhang et al, 2020). Our sequencing data showed that in 400 m, the distribution trend of 16S rRNA, amoA, and accA genes was highly consistent, confirming that the ammonia oxidation process of AOA and the fixation of carbon dioxide were mutually coupled in our culture experiments (Supplementary Figure S1).…”
Section: Stimulation Of Mgii In the Dcm Layer By Vertical Mixing Withsupporting
confidence: 84%
“…The radiocarbon signatures of thaumarchaeal DNA demonstrated that MGI members derive the majority of their carbon from inorganic carbon fixation from the same site (Hansman et al, 2009). A recent quantitative study of the amoA and accA genes in the western Pacific revealed similar distributional trends at depths greater than or equal to 100 m as those documented in our study (Zhang et al, 2020). Our sequencing data showed that in 400 m, the distribution trend of 16S rRNA, amoA, and accA genes was highly consistent, confirming that the ammonia oxidation process of AOA and the fixation of carbon dioxide were mutually coupled in our culture experiments (Supplementary Figure S1).…”
Section: Stimulation Of Mgii In the Dcm Layer By Vertical Mixing Withsupporting
confidence: 84%
“…N. vancouverensis" is also most closely related to the Nitrospinae clades 1 and 2 that are abundant in oligotrophic waters [20] (see above). However, its K m(app) is still 1-2 342 orders of magnitude higher than the K m(app) values of nitrite oxidation reported for environmental 343 samples from an OMZ (0.254±0.161 μM NO 2 -) and South China Sea waters (0.03 to 0.5 µM) 344 [22,57]. The very high nitrite affinity observed with these samples might be explained by the 345 presence of uncharacterized nitrite oxidizers, whose nitrite affinity exceeds that of all cultured 346 NOB.…”
Section: Nitrite Oxidation: Activity and Kinetics 311mentioning
confidence: 80%
“…In addition to their importance in the nitrogen cycle, the Nitrospinae have been suggested to play a major role in dark ocean carbon fixation by contributing up to 15-45% of the fixed inorganic carbon in some environments [20]. The contribution of Nitrospinae to CO 2 63 fixation is, however, still under debate [21,22], partially due to a lack of cultured representative 64 organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Strain KM1 had the lowest value among cultured NOB from non-marine habitats. According to a recent study, in situ kinetic values for nitrite oxidation in the dark ocean were at nanomolar levels and orders of magnitude lower than the K m(app) values of cultured NOB (Zhang et al, 2020). This would suggest uncultured NOB are well-adapted to oligotrophic environments in nature.…”
Section: Of Nitrospiramentioning
confidence: 96%